Testosterone Administration Related Differences in Brain Activation during the Ultimatum Game - Kopsida, Eleni; Berrebi, Jonathan; Petrovic, Predrag; Ingvar, Martin (Frontiers in Neuroscience, 2016)
A plethora of studies on the Ultimatum Game have shown that responders forfeit the rule of profit maximization and punish unfair proposers, by rejecting their offers. This behavior has been linked to increased amygdala, insula and dorsolateral prefrontal cortex activation. Studies have suggested a potential role of testosterone in the Ultimatum Game albeit with inconsistent findings. In the present study, we sought to further investigate the role of amygdala and testosterone in the Ultimatum Game, by conducting a double-blinded, single-administration study. 60mg of Tostrex was administered to male and female healthy volunteers, three hours prior to undergoing an fMRI session, during which they played a standard version of the Ultimatum Game. The behavioral analysis revealed a statistical trend, as participants in the testosterone group tended to accept a greater number of unfair offers than participants in the placebo group, irrespectively of gender. In terms of fMRI results, for the main contrast unfair>fair offers, the testosterone group displayed a greater activation in the right dlPFC compared to the placebo group. Increased testosterone levels were related to greater caudate activity. Our findings suggest a complex role of testosterone in social behavior and decision-making.